Non‐Small Cell Lung Cancer in Countries of Central and Southeastern Europe: Diagnostic Procedures and Treatment Reimbursement Surveyed by the Central European Cooperative Oncology Group. (3rd August 2018) - Ryska, Ales; Buiga, Rares; Fakirova, Albena; Kern, Izidor; Olszewski, Włodzimierz; Plank, Lukas; Seiwerth, Sven; Toth, Erika; Zivka, Eri; Thallinger, Christiane; Zielinski, Christoph; Brcic, Luka
Abstract: : This article analyzes the availability of different diagnostic procedures of non‐small cell lung cancer (NSCLC) and the reimbursement landscape of drugs for NSCLC in countries of central and southeastern Europe (CEE). A survey was conducted by the Central European Cooperative Oncology Group. Results of the survey show that both availability and reimbursement of diagnoses of molecular alterations in NSCLC, the detection of which is essential for therapeutic decisions, varies widely between countries of CEE. Not only is "reflex" testing often substituted by analyses performed only "on demand, " but reimbursement of such assessments varies widely between unavailability and payments by the health care system or even pharmaceutical companies. It was concluded that a structured access to testing and reimbursement should be the aim in order to provide patients with appropriate therapeutic options. Implications for Practice: This article provides an overview of the limitations in lung cancer treatment in countries of central and southeastern Europe, as well as the reimbursement status of various lung cancer treatment regimens in these countries, which directly impacts treatment options. Abstract : This article describes the results of a survey conducted by the Central European Cooperative Oncology Group to assess the availability of and reimbursement for molecular diagnostic tests and targeted therapies in non‐small cell lung cancer across ten countries in central and southeastern Europe.